2000
DOI: 10.1111/j.1530-0277.2000.tb04624.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of μ‐Opioid Receptor in the Salsolinol‐Associated Place Preference in Rats Exposed to Conditioned Fear Stress

Abstract: Salsolinol may have some rewarding effect, and its rewarding effect may be potentiated by psychological stress. In addition, the rewarding effect of salsolinol especially under psychological stress may involve the endogenous central opioid system, i.e., mu-opioid receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…According to this hypothesis, the blockade of the formation of these compounds (for example, through the inhibition of the ethanol metabolism in the brain) or their interaction with their targets, probably the opioid receptors (Critcher et al 1983;Myers et al 1986;Myers and Robinson 1999;Matsuzawa et al 2000), could suppress some of the behavioral consequences produced by ethanol administration. In that sense, local microinjections of ethanol or ACH into a DA-rich environment (such as the VTA) could lead to an increase in the local levels of THIQs.…”
Section: Discussionmentioning
confidence: 98%
“…According to this hypothesis, the blockade of the formation of these compounds (for example, through the inhibition of the ethanol metabolism in the brain) or their interaction with their targets, probably the opioid receptors (Critcher et al 1983;Myers et al 1986;Myers and Robinson 1999;Matsuzawa et al 2000), could suppress some of the behavioral consequences produced by ethanol administration. In that sense, local microinjections of ethanol or ACH into a DA-rich environment (such as the VTA) could lead to an increase in the local levels of THIQs.…”
Section: Discussionmentioning
confidence: 98%
“…Other authors also suggest this possibility. So, Matsuzawa et al (2000) showed that the blockade of the μ-opioid receptors significantly attenuated the place preference for Sal. Thus, one possible scenario is that Sal is responsible for some of the effects of ACH and ethanol through interactions with the μ-opioid receptors.…”
Section: Introductionmentioning
confidence: 98%
“…Systemic administration of Sal induces a slight place preference that can be potentiated under fear stress conditioning (Matsuzawa et al 2000). Rats learn to selfadminister this compound directly into the shell of the NAc (Rodd et al 2003) and directly into the ventral tegmental area (VTA; Rodd et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…All drugs were dissolved in saline and administered in a volume of 10 ml/kg. The pretreatment times and doses of naloxone, naloxone methiodide, and naloxonazine were based on our previous reports (Suzuki et al, 1995;Matsuzawa et al, 2000).…”
Section: Methodsmentioning
confidence: 99%